A HYDROTHERAPY IN THE ELDERLY: BALANCE AND FUNCTIONALITY (CIPEEX, 2022)
HYDROTHERAPY IS A PHYSIOTHERAPY TECHNIQUE THAT USES THE EFFECTS OF WATER AS A THERAPEUTICRESOURCE FOR THE PREVENTION AND REHABILITATION OF PATIENTS. IT BASICALLY CONSISTS OF THE PRACTICE OFEXERCISES IN THE POOL THAT, AT APPROPRIATE TEMPERATURES, AIM TO PROMOTE FUNCTIONAL GAINS,OFFERING A BETTER QUALITY OF LIFE FOR THE PATIENT. ITS THERAPEUTIC PURPOSES ARE DIRECTLY RELATED TOBALANCE STIMULATION, REDUCING THE RISK OF FALLS, GAIT STABILITY, PROMOTING THE EFFICIENT FUNCTIONINGOF THE SOMATOSENSORY, VISUAL AND VESTIBULAR SYSTEMS. THE PRESENT STUDY AIMS TO EVALUATE THEFUNCTIONAL PERFORMANCE AND BALANCE IN THE ELDERLY WHO PRACTICE HYDROTHERAPY, IN ADDITION TOIDENTIFYING THEIR SOCIODEMOGRAPHIC PROFILE.
Keywords: Hydrotherapy; Physiotherapy; Seniors; Functionality.